1996
DOI: 10.1254/jjp.72.111
|View full text |Cite
|
Sign up to set email alerts
|

Increased Inhibitory Effect of Phorbol Ester on Cytosolic Ca2+ Level and Contraction in Rat Myometrium after Gestation

Abstract: ABSTRACT-Activation of voltage-dependent Ca 21 channels by high K+ (40 mM) increased the cytosolic Ca2+ level ([Ca 2+]i) (estimated by fura-PE3 fluorescence ratio) and force in myometrium isolated from pregnant (21 days after gestation) and non-pregnant (estrus) rats. 12-Deoxyphorbol 13-isobutyrate (DPB, 1 mM) decreased the high K+-stimulated [Ca 2+]i and force in a concentration-dependent manner. The inhibitory effect was stronger in the pregnant myometrium than in the non-pregnant myometrium. In the pregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
11
1
Order By: Relevance
“…In the light of the awareness of species‐related differences in PKC‐mediated signaling, we attempted to examine the effects of PKC activation on [Ca 2+ ] i and contraction in myometrium isolated from pregnant and nonpregnant women. We found that PKC activation induces positive feedback control in the activation processes of the smooth muscle contractile element in human myometrium, which is distinct from findings in rat myometrium showing that PKC is involved in the negative feedback control of the contractile mechanism (Savineau & Mironneau, 1990; Kim et al , 1996 ).…”
Section: Introductioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In the light of the awareness of species‐related differences in PKC‐mediated signaling, we attempted to examine the effects of PKC activation on [Ca 2+ ] i and contraction in myometrium isolated from pregnant and nonpregnant women. We found that PKC activation induces positive feedback control in the activation processes of the smooth muscle contractile element in human myometrium, which is distinct from findings in rat myometrium showing that PKC is involved in the negative feedback control of the contractile mechanism (Savineau & Mironneau, 1990; Kim et al , 1996 ).…”
Section: Introductioncontrasting
confidence: 69%
“…In the myometrium isolated either from pregnant or nonpregnant rat, it has been reported that phorbol ester induces inhibitory effects on contraction (Savineau & Mironneau, 1990; Phillippe, 1994a,1994b). We have also observed decreases in [Ca 2+ ] i and muscle contraction upon PKC stimulation by phorbol ester in rat myometrium, showing that PDBu inhibits the increase in [Ca 2+ ] i more strongly in myometrium from pregnant than from nonpregnant rats ( Kim et al , 1996 ). In contrast to the results in rat myometrium, others have suggested the importance of PKC in the agonist‐induced contractions in human myometrium ( Morrison et al , 1996 ; Breuiller‐Fouche et al , 1998 ; Eude et al , 2000 ).…”
Section: Introductionmentioning
confidence: 63%
“…It has been reported that PKC activation by phorbol ester inhibits gastric smooth muscle contractions by inhibiting inositol phosphate production , but induces vascular and tracheal smooth muscle contractions by increasing the Ca 2C sensitivity of contractile elements (Morgan & Morgan 1984, Sato et al 1988, Ozaki et al 1990, Sato et al 1992. In rat myometrial cells, the PKC activation inhibits Ca 2C channel activity (Kusaka & Sperelakis 1995), and thus PKC activation in the rat myometrium has an inhibitory effect on contractions (Baraban et al 1985, Savineau & Mironneau 1990, Phillippe 1994, Kim et al 1996. In contrast, in cultured cells of rat portal veins, PKC activation increases Ca 2C channel activity (Loirand et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Some drugs are also known to contract smooth muscle 2,3) . Many previous studies, including our own, have reported on signal transduction mechanisms and smooth muscle contractions [4][5][6][7][8][9][10][11][12][13][14] . In spite of the importance of the smooth muscle in the fields of cardiovascular physiotherapy, obstetrics, and clinical methods, there is still a need for more research [15][16][17] .…”
Section: Introductionmentioning
confidence: 87%
“…The activated MLCK phosphorylates the 20-kDa serine residue of myosin light chain (MLC 20 ), which leads to muscle contraction by increasing the activation of myosin-Mg 2+ ATPase (Fig. 1A) [1][2][3][4] . Additionally, receptors activated by agonists such as prostaglandin F2α (PGF2α), endothelin-1 (ET-1), and norepinephrine cause conformational changes in the receptors and activate GTP-binding protein (or G-protein).…”
Section: The Mechanisms Of Smooth Muscle Contraction 1) Myosin Light mentioning
confidence: 99%